Enough et too : expression de la suffisance et de l’excès dans les constructions « tough » en anglais - Joasha Boutault (Corela)
In English, the structures known as “tough” constructions (The decision was easy to make), enable the speaker to predicate a property of the subject, interpreted as co-referent of the internal argument of the infinitival verb. Therefore, some kind of evaluation has to be present. In “classical” examples such as they will be difficult to convince, the adjectives play this role : difficult is evaluative in itself. When the adjective is descriptive, as in this area is too spread out to defend, the presence of too or enough is compulsory. In those cases, the adverb is what provides the necessary evaluation. Through the study of authentic examples, this article shows how too and enough contribute to the evaluative interpretation of “tough” constructions. When they are used in such structures, these adverbs respectively prevent and enable the realisation of the event denoted by the infinitival verb. The point of view of the speaker on the possibility for the predicative relation to be validated is thus expressed.